Radioactive element adsorbent containing aluminum silicate and its manufacturing method

An aluminum silicate adsorbent with tailored properties effectively removes cesium, cobalt, and strontium from nuclear waste, addressing disposal challenges and enhancing nuclear power plant efficiency.

JP7599748B2Active Publication Date: 2024-12-16GIANT CHEM CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023196741
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2023-09-25
Filing Date
2023-11-20
Publication Date
2024-12-16
Estimated Expiration
2043-11-20

AI Technical Summary

Technical Problem

The disposal of radioactive waste from nuclear power plants is challenging due to the presence of cesium, cobalt, and strontium, which are difficult to remove efficiently due to their high solubility and reactivity, leading to contamination and operational inefficiencies in nuclear power plants.

Method used

A radioactive element adsorbent comprising aluminum silicate with controlled pore size, specific surface area, and elemental composition is synthesized to effectively adsorb cesium, cobalt, and strontium, optimized by adjusting the aluminum and silicon content and pore diameter.

Benefits of technology

The adsorbent achieves high removal efficiencies of 95-100% for cesium, cobalt, and strontium, improving nuclear power plant operations by reducing contamination and enhancing heat transfer efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007599748000013
    Figure 0007599748000013
  • Figure 0007599748000014
    Figure 0007599748000014
  • Figure 0007599748000015
    Figure 0007599748000015
Patent Text Reader

Abstract

To provide a radioactive element adsorbent containing aluminum silicate and a method of manufacturing the same.SOLUTION: The present invention relates to an aluminum silicate-containing adsorbent for radioactive elements such as cesium, cobalt, and strontium, and a method of manufacturing the same. The present invention can specify the pore size, specific surface area, element content, and oxide content of the aluminum silicate that optimize radioactive element adsorption efficiency.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a radioactive element adsorbent containing aluminum silicate (aluminum silicate) and a method for producing the same, and more particularly to a radioactive element adsorbent containing aluminum silicate for cesium, cobalt and strontium and a method for producing the same. [Background technology]

[0002] Nanoporous materials with large specific surface areas and uniform pores are widely used as adsorbents, catalyst supports, separation and purification processes, and ion exchange media. In particular, the synthesis of novel nanostructured materials with controlled porosity is an ongoing area of ​​research in the field of new materials.

[0003] Among them, aluminum silicate is a porous inorganic chemical substance synthesized by the precipitation reaction of water soluble aluminum salts and sodium silicate, and due to its strong adsorption properties, it is used in industrial fields, food refining, cosmetics raw materials, etc.

[0004] Meanwhile, as the world becomes increasingly dependent on nuclear power plants for energy, the disposal of radioactive waste that may result from a nuclear accident has emerged as a major issue.

[0005] Radioactive cesium ( 137 Cs is the main cause of radioactive contamination from nuclear power plant accidents, nuclear waste, etc. It has high solubility in water, a long half-life, and behaves similarly to potassium ions in the body, so even if it is absorbed into the body it is not excreted properly and can cause various cancers, including lung cancer and bone marrow cancer. Therefore, there is an emerging need for technology to remove this radioactive cesium.

[0006] Cobalt (Co) is a radioactive nuclide that does not exist in nature, and when exposed to high temperature and pressure during the operation of a nuclear power plant, it reacts with water and dissolved oxygen to form corrosion products, and together with radioactive materials emitted from the nuclear fuel, it forms an oxide film on the cooling water pipeline. The oxide film formed at this time is made up of components of the coolant contact equipment, such as iron, chromium, nickel, copper, and cobalt, and reduces the efficiency of heat transfer required for cooling, causing a decrease in the operating efficiency of the nuclear power plant.

[0007] Strontium (Sr) is a soft, silvery-white alkaline earth metal that is softer and more reactive than calcium. It reacts violently in water to produce strontium hydroxide (Sr(OH)2) and hydrogen gas (H2), and burns in air to produce strontium oxide and strontium nitride. Cesium and strontium are radioactive contaminant nuclides that are formed in large quantities during the nuclear fission of uranium, and because they have the property of releasing high amounts of heat and a half-life of more than 30 years, they must be removed from radioactive contaminated water.

[0008] However, radioactive liquid waste contains various chemical substances, and due to foaming and corrosion during operation, the operating conditions are strict and smooth processing is difficult. Therefore, methods using adsorbents to efficiently remove radioactive elements are being considered. [Prior art documents] [Patent documents]

[0009] [Patent Document 1] Korean Patent Publication No. 10-2018-0050190 Summary of the Invention [Problem to be solved by the invention]

[0010] An object of the present invention is to provide a radioactive element adsorbent comprising aluminum silicate capable of adsorbing cesium, cobalt and strontium.

[0011] Another object of the present invention is to specify the pore size, specific surface area, element and oxide content of said aluminum silicate, which can optimize the cobalt removal efficiency.

[0012] It is still another object of the present invention to provide a method for producing a cesium, cobalt and strontium radioactive element adsorbent containing said aluminum silicate.

[0013] The technical problems that the present invention aims to solve are not limited to the technical problems mentioned above, and other technical problems not mentioned will also be clearly understood by a person having ordinary skill in the art from the description of the present invention. [Means for solving the problem]

[0014] The present invention provides a radioactive element adsorbent comprising an aluminum silicate.

[0015] In the present invention, the radioactive element is one or more elements selected from the group consisting of cesium, cobalt, and strontium.

[0016] In the present invention, the aluminum silicate has a pore diameter of 30.5 to 32.5 Å and a specific surface area of ​​500 to 600 m 2 / g.

[0017] In the present invention, the aluminum silicate is characterized in that the aluminum (Al) content is 10-12 wt %, the silicon (Si) content is 28-31 wt %, and the aluminum:silicon (Al:Si) ratio is 1:2-3.

[0018] In the present invention, the aluminum silicate is characterized in that the Al2O3 content is 23 to 25 wt%, the SiO2 content is 70 to 73 wt%, and the Al2O3:SiO2 ratio is 1:2.5 to 3.5.

[0019] The present invention provides a method for producing a radioactive element adsorbent containing aluminum silicate, comprising the steps of: diluting one or more water-soluble aluminum salts selected from the group consisting of aluminum nitrate, aluminum sulfate, and aluminum chloride with water to produce an aluminum salt dilute solution having a concentration of 10 to 20% by weight; mixing the produced aluminum salt dilute solution with a silicate precursor to synthesize aluminum silicate at 20 to 60°C; and washing the synthesized aluminum silicate with water and drying it.

[0020] In the present invention, the method for producing a radioactive element adsorbent containing aluminum silicate is characterized by further comprising a step of adding one or more pH adjusters selected from the group consisting of ammonium nitrate, ammonium citrate, and sodium citrate to the aluminum salt dilute solution. Effect of the Invention

[0021] The present invention can provide a radioactive element adsorbent containing aluminum silicate capable of adsorbing cesium, cobalt, and strontium.

[0022] In addition, the present invention can embody the pore size, specific surface area, element and oxide contents of the aluminum silicate, which can optimize the cobalt removal efficiency.

[0023] Furthermore, the present invention can provide a method for producing an adsorbent for radioactive elements of cesium, cobalt and strontium, which contains the aluminum silicate.

[0024] The effects of the present invention are not limited to those mentioned above, and other effects not mentioned will be clearly understood by those skilled in the art from the description of the claims. [Brief description of the drawings]

[0025] [Figure 1] FIG. 1 is a schematic diagram showing a synthesis process of aluminum silicate according to the present invention. [Diagram 2] 1 is a photograph showing the color change of aluminum silicate according to the present invention after cesium adsorption. [Diagram 3] 1 is a photograph showing the color change of aluminum silicate according to the present invention after cobalt adsorption. [Figure 4] 1 is a photograph showing the color change of the aluminum silicate according to the present invention after adsorption of strontium. [Diagram 5] FIG. 2 is a schematic diagram showing the adsorption mechanism of radioactive elements by aluminum silicate according to the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0026] The terms used in this specification are selected as widely used as possible while taking into consideration the functions of the present invention, but they may vary depending on the intentions of those skilled in the art, precedents, or the emergence of new technology. In addition, in certain cases, the applicant may arbitrarily select a term, and in such cases, the meaning of the term will be described in detail in the description of the invention. Therefore, the terms used in this specification are defined based on the meaning of the term and the overall content of the present invention, rather than simply the name of the term.

[0027] Unless otherwise defined, all terms used herein, including technical or scientific terms, have the same meaning as commonly understood by a person of ordinary skill in the art to which this invention pertains. Terms as defined in commonly used dictionaries are to be interpreted as having a meaning consistent with the meaning they have in the context of the relevant art, and are not to be interpreted as idealized or overly formal unless expressly defined in this application.

[0028] Numeric ranges are inclusive of the numerical values ​​defined in the range. Every maximum numerical limitation given herein includes every lower numerical limitation, as if a lower numerical limitation is expressly stated. Every minimum numerical limitation given herein includes every higher numerical limitation, as if a higher numerical limitation is expressly stated. Every numerical limitation given herein includes every greater numerical range within a broader numerical range, as if a narrower numerical limitation is expressly stated.

[0029] The present invention will be described in detail below.

[0030] Radioactive element adsorbents containing aluminum silicate The present invention provides a radioactive element adsorbent comprising an aluminum silicate.

[0031] The radioactive element may be one or more selected from the group consisting of cesium, cobalt and strontium, and may be preferably cobalt.

[0032] The pore size of the aluminum silicate may be 30.5 to 32.5 Å, and preferably 31 to 32 Å.

[0033] The weight of the aluminum silicate may be 0.2 to 0.3 g, and preferably 0.22 to 0.26 g.

[0034] The specific surface area of ​​the aluminum silicate is 500 to 600 m 2 / g, preferably 520 to 580m 2 / g.

[0035] The pore volume of the aluminum silicate is 0.4~0.5cm 3 / g, preferably 0.4 to 0.46 cm 3 / g.

[0036] The cesium removal efficiency of the aluminum silicate may be 95 to 100%, and preferably 97 to 100%. The cesium removal efficiency may be calculated according to the following formula 1, in which C i is the initial metal ion concentration, and C f may be the metal ion concentration after adsorption.

[0037] Similarly, the cobalt removal efficiency of the aluminum silicate may be 95 to 100%, and preferably 97 to 100%. The cobalt removal efficiency may be calculated according to the following formula 1, in which C i is the initial metal ion concentration, and C f may be the metal ion concentration after adsorption.

[0038] Similarly, the strontium removal efficiency of the aluminum silicate may be 95 to 100%, and preferably 97 to 100%. The strontium removal efficiency may be calculated according to the following formula 1, in which C i is the initial metal ion concentration, and C f may be the metal ion concentration after adsorption.

[0039]

number

[0040] The aluminum silicate is capable of adsorbing the radioactive element cobalt and can turn pink upon adsorbing cobalt.

[0041] The aluminum silicate may have an aluminum (Al) content of 10 to 12 wt%, a silicon (Si) content of 28 to 31 wt%, and an aluminum:silicon (Al:Si) ratio of 1:2 to 3. Preferably, the aluminum silicate may have an aluminum (Al) content of 11.6 wt%, a silicon (Si) content of 29.3 wt%, and an aluminum:silicon (Al:Si) ratio of 1:2.52.

[0042] The aluminum silicate may have an Al2O3 content of 23-25 ​​wt%, an SiO2 content of 70-73 wt%, and an Al2O3:SiO2 ratio of 1:2.5-3.5. Preferably, the aluminum silicate may have an Al2O3 content of 24.1 wt%, an SiO2 content of 71.6 wt%, and an Al2O3:SiO2 ratio of 1:2.97.

[0043] Method for producing radioactive element adsorbent containing aluminum silicate The present invention provides a method for producing a radioactive element sorbent comprising aluminum silicate.

[0044] The method for producing the radioactive element adsorbent may include the steps of: diluting one or more water-soluble aluminum salts selected from the group consisting of aluminum nitrate, aluminum sulfate, and aluminum chloride with water to produce an aluminum salt dilute solution having a concentration of 10 to 20% by weight; mixing the produced aluminum salt dilute solution with a silicate precursor to synthesize aluminum silicate at 20 to 60°C; and washing the synthesized aluminum silicate with water and drying it.

[0045] In addition, the method for producing the radioactive element adsorbent may further include a step of adding one or more pH adjusters selected from the group consisting of ammonium nitrate, ammonium citrate, and sodium citrate to the produced aluminum salt dilute solution, and preferably ammonium nitrate may be used as the pH adjuster.

[0046] The step of diluting one or more water-soluble aluminum salts selected from the group consisting of aluminum nitrate, aluminum sulfate, and aluminum chloride with water to produce an aluminum salt diluted solution having a concentration of 10 to 20 wt % may be a step of diluting one or more water-soluble aluminum salts selected from the group consisting of aluminum nitrate, aluminum sulfate, and aluminum chloride with water to a concentration of 10 to 20% (w / v) to produce an aluminum salt diluted solution that is a transparent solution.

[0047] The step of mixing the produced aluminum salt diluted solution with a silicate precursor and synthesizing aluminum silicate at 20 to 60°C is a step of synthesizing aluminum silicate by injecting a silicate precursor into the produced aluminum salt diluted solution at a uniform rate, and one or more pH adjusters selected from the group consisting of ammonium nitrate, ammonium citrate, and sodium citrate may be added to the aluminum salt diluted solution as described above.

[0048] The silicate precursor may be at least one selected from the group consisting of silica (SiO2), sodium silicate, tetramethyl orthosilicate, tetraethyl orthosilicate, tetrapropyl orthosilicate, triethoxyethylsilane (TEES), and 1,2-bis(triethoxysilyl)ethane (BTSE), and is preferably sodium silicate.

[0049] In the step of synthesizing aluminum silicate at 20 to 60°C by mixing the prepared aluminum salt dilute solution with a silicate precursor, the aluminum silicate can be synthesized at 20 to 60°C for 10 to 50 minutes according to the synthesis conditions, and the ratio of silicon atoms to aluminum atoms (Si / Al) can be 2 to 5.

[0050] The step of washing and drying the synthesized aluminum silicate is a step of removing impurities remaining on the surface of the synthesized aluminum silicate, and the particles can be washed with water, preferably washed 2 to 4 times with water, and then dried in a drying oven set at 80 to 120°C for 1 to 3 hours.

[0051] EXAMPLES The present invention will be described in detail below with reference to examples, but it goes without saying that the present invention is not limited to these examples.

[0052] Example 1. Preparation of radioactive element adsorbent containing aluminum silicate 1-1. Reagents and materials Aluminum sulfate octadecahydrate, aluminum nitrate nonahydrate, aluminum chloride hexahydrate, cetyltrimethylammonium bromide, and ammonium bicarbonate were purchased from Samchun chemicals. Ammonium hydroxide, sodium citrate, ammonium nitrate, ammonium citrate, and methanol were purchased from Daejung Chemicals. Pluronic P123, Sigma Aldrich, and Konix KE-810 were purchased and used from KPX Chemicals. Sodium silicate (29%), used as a silicate precursor, was purchased from Ihlshin Chemical.

[0053] 1-2. Synthesis of aluminum silicate Aluminum silicate was synthesized by the precipitation reaction of aluminum sulfate (Al(SO4)3) and sodium silicate (14.5%). Specifically, aluminum sulfate (Al(SO4)3) was diluted with water to a concentration of 16.5%, and stirred until a transparent solution was obtained to produce an aluminum salt dilute solution. Ammonium nitrate, a pH adjuster, was added to the aluminum salt dilute solution, and the pH was adjusted by stirring and heating. Then, sodium silicate was injected into the aluminum salt dilute solution at a uniform rate using a metering pump to synthesize aluminum silicate. In the injection step, the ratio of silicon atoms to aluminum atoms (Si / Al) was set to 3.5, and the solution was stirred at 150 rpm using a magnet bar, and synthesis was performed at a synthesis temperature of 40°C for 30 minutes.

[0054] 1-3. Washing and drying of aluminum silicate In order to remove residual impurities on the surface of the aluminum silicate prepared in Example 1-2, the particles were washed with water. Specifically, the particles were washed with 1 L of water three times in total, and then dried in a drying oven set at 105° C. for 2 hours.

[0055] Comparative Example 1. Production of aluminum silicate with adjusted aluminum sulfate concentration In order to confirm the effect of aluminum sulfate concentration on the adsorption ability of radioactive elements, aluminum silicate was prepared by adjusting the aluminum sulfate concentration from 16.5% to 8.25%. This aluminum silicate was prepared in the same manner as the aluminum silicate in Example 1, except for the aluminum sulfate concentration.

[0056] Comparative Example 2. Production of illite In the case of illite, it is usually first extracted from the mine and then processed through a separate crushing and drying process.

[0057] Experimental Example 1. Analysis of the specific surface area of ​​the aluminum silicate according to the present invention Experimental Example 1 was carried out to perform a specific surface area analysis (BET) of the aluminum silicate and illite prepared in Example 1, Comparative Example 1, and Comparative Example 2. In Experimental Example 1, the specific surface area, pore volume, and pore size were analyzed, and the results of Experimental Example 1 are shown in Table 1.

[0058] As a result of this Experimental Example 1, the specific surface area of ​​the aluminum silicate prepared in Example 1 was 551.2568 m 2 / g and the pore volume is 0.4339 cm 3 The aluminum silicate prepared in Comparative Example 1 had a specific surface area of ​​212.93 m 2 / g and the pore volume is 0.7474 cm 3 The pore size was confirmed to be 33.715 Å / g and the specific surface area of ​​the illite prepared in Comparative Example 2 was 10.1502 m 2 / g and the pore volume is 0.0292 cm 3 / g and the pore diameter was confirmed to be 115.30 Å (Table 1).

[0059] [Table 1]

[0060] Experimental Example 2. Cesium removal efficiency of aluminum silicate according to the present invention Experimental Example 2 was carried out to examine the cesium (Cs) removal efficiency of the aluminum silicate and illite prepared in Example 1, Comparative Example 1 and Comparative Example 2.

[0061] 126 mg of cesium chloride was dissolved in 1 L of distilled water and dispersed for 10 minutes using ultrasonic vibration. 100 mL of the dispersion was stirred at 300 rpm, and 1 g of each of the aluminum silicate or illite adsorbent prepared in Example 1, Comparative Example 1, or Comparative Example 2 was added. The mixed solution of the dispersion and the adsorbent was centrifuged at 8000 rpm for 5 minutes to separate the supernatant. The residual cesium concentration of the supernatant was confirmed by inductively coupled plasma-mass spectrometry (ICP-MS), and the results of Experimental Example 2 are shown in Table 2 below.

[0062] As a result of Experimental Example 2, the cesium removal efficiency of Example 1 was 99.70%, the cesium removal efficiency of Comparative Example 1 was 99.74%, and the cesium removal efficiency of Comparative Example 2 was 21.0%. The cesium removal efficiency was calculated according to the following formula 1, where C i is the initial metal ion concentration, and C f means the metal ion concentration after adsorption.

[0063]

number

[0064] [Table 2]

[0065] Experimental Example 3. Color change of aluminum silicate according to the present invention after cesium adsorption Experimental Example 3 was carried out to observe the color change of the aluminum silicate and illite produced in Example 1, Comparative Example 1 and Comparative Example 2 after cesium adsorption. The cesium adsorption method using the aluminum silicate or illite was carried out in the same manner as in Experimental Example 2. The results of observing the color change of the aluminum silicate and illite after cesium adsorption are shown in FIG. 2.

[0066] As a result of Experimental Example 3, no color change was observed in any of the aluminum silicates and illite of Example 1, Comparative Example 1, and Comparative Example 2 after cesium adsorption (FIG. 2).

[0067] Experimental Example 4. Comparison of cobalt removal efficiency of aluminum silicates according to the present invention Experimental Example 4 was carried out to confirm the cobalt removal efficiency of the aluminum silicate and illite prepared in Example 1, Comparative Example 1 and Comparative Example 2.

[0068] 493.8 mg of cobalt nitrate was dissolved in 1 L of distilled water and dispersed for 10 minutes using ultrasonic vibration. 100 mL of the dispersion was stirred at 300 rpm, and 1 g of each of the aluminum silicate or illite adsorbent prepared in Example 1, Comparative Example 1, or Comparative Example 2 was added. The mixed solution of the dispersion and the adsorbent was centrifuged at 8000 rpm for 5 minutes to separate the supernatant. The residual cobalt concentration of the supernatant was confirmed by inductively coupled plasma-mass spectrometry (ICP-MS), and the results of Experimental Example 4 are shown in Table 3 below.

[0069] As a result of Experimental Example 4, the cobalt removal efficiency of Example 1 was 98.14%, the cobalt removal efficiency of Comparative Example 1 was 82.40%, and the cobalt removal efficiency of Comparative Example 2 was 10.1%. The cobalt removal efficiency was calculated according to Equation 1, where C i is the initial metal ion concentration, and C f means the metal ion concentration after adsorption.

[0070] [Table 3]

[0071] Experimental Example 5. Color change of aluminum silicate according to the present invention after adsorption of cobalt Experimental Example 5 was carried out to observe the color change after cobalt adsorption of the aluminum silicate and illite prepared in Example 1, Comparative Example 1 and Comparative Example 2. The method of adsorbing cobalt using the aluminum silicate according to Example 1 was carried out in the same manner as in Experimental Example 4. The color change of the aluminum silicate and illite after cobalt adsorption is shown in FIG.

[0072] As a result of Experimental Example 5, the aluminum silicate of Example 1 changed color to pink after adsorbing cobalt, whereas the aluminum silicate of Comparative Example 1 and the illite of Comparative Example 2 did not change color after adsorbing cobalt (FIG. 3).

[0073] Experimental Example 6. Comparison of strontium removal efficiency of aluminum silicate according to the present invention Experimental Example 6 was carried out to confirm the strontium removal efficiency of the aluminum silicate and illite prepared in Example 1, Comparative Example 1 and Comparative Example 2.

[0074] 180.9 mg of strontium chloride was dissolved in 1 L of distilled water and dispersed for 10 minutes using ultrasonic vibration. 100 mL of the dispersion was stirred at 300 rpm, and 1 g of each of the aluminum silicate or illite adsorbent prepared in Example 1, Comparative Example 1, or Comparative Example 2 was added. The mixed solution of the dispersion and the adsorbent was centrifuged at 8000 rpm for 5 minutes to separate the supernatant. The residual strontium concentration of the supernatant was confirmed by inductively coupled plasma-mass spectrometry (ICP-MS), and the results of Experimental Example 6 are shown in Table 4 below.

[0075] As a result of Experimental Example 6, the strontium removal efficiency was 99.76% in Example 1, 99.06% in Comparative Example 1, and 16.0% in Comparative Example 2. The strontium removal efficiency was calculated according to Equation 1.

[0076] [Table 4]

[0077] Experimental Example 7. Color change of aluminum silicate according to the present invention after adsorption of strontium Experimental Example 7 was carried out to observe the color change after strontium adsorption of the aluminum silicate and illite prepared in Example 1, Comparative Example 1 and Comparative Example 2. The strontium adsorption method using the aluminum silicate and illite was carried out in the same manner as in Experimental Example 6. The color change of the aluminum silicate after strontium adsorption is shown in FIG.

[0078] As a result of Experimental Example 7, no color change was observed in the aluminum silicate and illite prepared in Example 1, Comparative Example 1, and Comparative Example 2 after strontium adsorption (FIG. 4).

[0079] Experimental Example 8. Elemental content of aluminum silicate according to the present invention The aluminum silicate and illite produced in Example 1, Comparative Example 1 and Comparative Example 2 were analyzed for elemental contents.

[0080] We used our own EMCRAFT SEM (CUBE II) and the attached EDS detector (Xplore compact 30) and AZtecOne program to perform a compositional analysis of aluminum silicate and illite.

[0081] As a result of this Experimental Example 8, the aluminum silicate of Example 1 had an Al:Si ratio of 1:2.08, and the adsorption capacity of radioactive elements cesium, cobalt, and strontium was the best at this ratio (Table 5). This is considered to be because the specific surface area of ​​the aluminum silicate of Example 1 is high, and water containing radioactive ions is absorbed between the aluminum silicate layers, which not only forms a negative channel for oxygen atoms between the aluminum silicate layers, but also increases the space in which the radioactive ions are sandwiched, resulting in their removal (see FIG. 5). In the case of the illite produced in Comparative Example 2, the silicate ratio is high, but K, Fe, and Al ions coexist, which is considered to lower the adsorption capacity of radioactive elements cesium, cobalt, and strontium.

[0082] [Table 5]

[0083] Experimental Example 9. Analysis of adsorption capacity by ion size of radioactive elements Cesium (Cs + ), Cobalt (Co 2+ ) and strontium (Sr 2+The ion sizes of radioactive elements such as cesium (Cs) are shown in Table 6 below, and the adsorption capacity according to the ion size is compared. + ) has an ion size of 169 pm, and cobalt (Co 2+ ) has an ion size of 72 pm, and strontium (Sr 2+ The ion size of cobalt (Co) is 113 pm. 2+ )< Strontium (Sr 2+ )<Cesium (Cs + ) order, this is because there is enough space between the negative channels in the aluminum silicate, and strontium (Sr 2+ ), Cesium (Cs + ), Cobalt (Co 2+ It can be concluded that this is because of the high efficiency of removing ions.

[0084] [Table 6]

[0085] Experimental Example 10. XRF Analysis of Aluminum Silicate The aluminum silicates prepared in Example 1 and Comparative Example 1 were subjected to XRF analysis. The XRF analysis was performed in the range of nitrogen to curium using a ZSX Primus IV (Rigaku) ​​instrument, and detection was performed using a scintillation counter (SC) and a flow proportional counter (F-PC). The results of Experimental Example 10 are shown in Tables 7 and 8.

[0086] [Table 7]

[0087] [Table 8]

[0088] As a result of this Experimental Example 10, it was confirmed that the element contents of the aluminum silicate produced in the Example 1 were oxygen (O) 56.1wt%, silicon (Si) 29.3wt%, aluminum (Al) 11.6wt%, sodium (Na) 1.9wt%, fluorine (F) 0.5wt%, calcium (Ca) 0.2wt%, potassium (K) 0.1wt%, sulfur (S) 0.1wt%, and others (Mg, Ti, etc.) 0.1wt%. The element contents of the aluminum silicate produced in the Comparative Example 1 were confirmed to be oxygen (O) 56.5wt%, silicon (Si) 34.6wt%, aluminum (Al) 7.0wt%, sodium (Na) 1.6wt%, fluorine (F) 0.3wt%, and others (S, Fe, etc.) 0.1wt% (Table 7).

[0089] In addition, the oxide contents of the aluminum silicate produced in Example 1 were confirmed to be 71.6 wt% SiO2, 24.1 wt% Al2O3, 2.8 wt% Na2O, 0.6 wt% F, 0.3 wt% SO3, 0.3 wt% CaO, 0.2 wt% K2O, and 0.2 wt% others (MgO, TiO2, etc.). The oxide contents of the aluminum silicate produced in Comparative Example 1 were confirmed to be 82.9 wt% SiO2, 14.4 wt% Al2O3, 2.3 wt% Na2O, 0.3 wt% F, 0.1 wt% SO3, and 0.09 wt% others (CaO, Fe2O3, etc.).

[0090] More specifically, the results of Experimental Example 10 were similar in the aluminum silicates prepared in Example 1 and Comparative Example 1 in terms of the contents of elements other than Si and Al, but the contents of Si and Al were different. The Al:Si ratio of the aluminum silicate prepared in Example 1 was 11.6:29.3, i.e., 1:2.52, and the Al:Si ratio of the aluminum silicate prepared in Comparative Example 1 was 7.0:34.6, i.e., 1:4.94. The Al:Si ratios are shown in Table 9 below.

[0091] [Table 9]

[0092] Similarly, the aluminum silicates prepared in Example 1 and Comparative Example 1 had similar contents of oxides other than Al2O3 and SiO2 oxides, but different contents of Al2O3 and SiO2. The Al2O3:SiO2 ratio of the aluminum silicate prepared in Example 1 was 24.1:71.6, i.e., 1:2.97, and the Al2O3:SiO2 ratio of the aluminum silicate prepared in Comparative Example 1 was 14.4:82.9, i.e., 1:5.75. The Al2O3:SiO2 ratios are shown in Table 10 below.

[0093] [Table 10]

[0094] From the above description, those skilled in the art in the art to which the present invention pertains can understand that the present invention can be embodied in other specific forms without changing the technical spirit or essential characteristics of the present invention. In this regard, the above-described embodiments are illustrative in all respects and are not restrictive.

Claims

1. A radioactive element adsorbent containing aluminum silicate and adsorbing cobalt and strontium as radioactive elements, The pore diameter is 30.5 to 32.5 Å, the specific surface area is 500 to 600 m 2 / g, and the pore volume is 0.4 to 0.5 cm 3 / g; The aluminum content is 10-12 wt %, the silicon content is 28-31 wt %, and the aluminum to silicon ratio (Al:Si) is 1:2-3; The content of Al 2 O 3 is 23 to 25 wt %, the content of SiO 2 is 70 to 73 wt %, and the ratio of Al 2 O 3 to SiO 2 (Al 2 O 3 :SiO 2 ) is 1:2.5 to 3.

5. A radioactive element adsorbent characterized by:

2. diluting aluminum sulfate with water to produce a dilute aluminum salt solution having a concentration of 10-20% by weight; adding a pH adjuster for ammonium nitrate to the dilute aluminum salt solution; mixing the aluminum salt dilute solution to which the pH adjuster has been added with sodium silicate to synthesize aluminum silicate at 20 to 60° C. for 10 to 50 minutes, and synthesizing the aluminum salt dilute solution and the sodium silicate in such a way that the ratio of silicon atoms to aluminum atoms (Si / Al) is 2 to 5; washing the synthesized aluminum silicate with water and then drying it at 80 to 120° C. for 1 to 3 hours; Includes A method for producing a radioactive element adsorbent containing aluminum silicate, comprising:

Citation Information

Patent Citations

  • Process of radioactive waste liquid

    JP1993034497A

  • ION ADSORBENT, Cs RECOVERY METHOD AND DEVICE USING THE SAME, AND ELECTRONIC APPARATUS

    JP2023116407A

  • Quasi-2d perovskite film, photoluminescence device and solar cell including the same, and method of preparing the same

    KR1020180050190A

  • Aluminum silicate and method for producing same

    WO2013183742A1